FamilySense: ferramenta computacional para jogos terapêuticos culturalmente contextualizados - Villena, Johana María Rosas (2010)
It is described in this Dissertation a computational tool named FamilySense, which aims to support the therapist to create contextualized games according to the profile of each family in therapy, in order to allow this family to identify and understand it the existing vocabulary. As a research contribution in the computering area, more specifically, describes the process model defined for the creation and design of FamilySense computational tool. This tool is inspired in a board game used primarily between members of the same family and / or the therapist in therapeutic sessions with families to allow their members to know each other. In this context, there was necessary identify the characteristics and elements of that game as well as the way it's played therefore he could be mapped to the computer. Using this process could be identified, and further on map, computational resources that could be aggregated to FamilySense, such as multimedia resources. Another contribution is the use of cultural knowledge expressed in the base of the Open Mind Common Sense project in Brazil to support the creation of the game and its content. The therapist as a coauthor, can use this cultural knowledge to create contextualized games according to the principle and therapeutic goal, for example, can identify possible problems in relationships between members of a family, to promote interaction between members of a family to identify possible issues to be worked out during therapy, etc.. Aiming to observe the use of this tool in a therapeutic environment and collect the opinions of the target group, case studies were conducted with therapists and families, reported in this research, to verify the feasibility of the proposal and its proof of concept.